Studies to elucidate host immune mechanisms involved in the blastocystis sp. subtype 3 symptomatic and asymptomatic infection / Sheela Devi Sugadan - Sheela Devi, Sugadan (2019)
Blastocystis sp. is an enteric protozoan parasite of humans and many animals. Blastocystis sp. ST3 proves to be the highest frequency case in most populations around the world and it is further distinguished into symptomatic and asymptomatic isolates based on the clinical symptoms exhibited by infected individuals. Phenotypic and genotypic studies implicate the distinctiveness of this parasite. However, the pathogenesis of this parasite is still in a grey area. Therefore, this study was aimed to analyse the immunopathogenesis of Blastocystis sp. ST3 symptomatic and asymptomatic isolates. The immunopathogenesis of this parasite was analysed by assessing the (1) characteristic of antigen immune response (antigen specificity and diversity) and (2) the modulations of innate and adaptive immune responses. The antigen specificity was evaluated by immunising Balb/c mice with 20Âµg/ml solubilised antigen. Results has shown pre?dominant of Th1 (IFN? and IL-2) cytokine response and IgG2a antibody response induced by symptomatic antigen immunised group and pre-dominant of Th2 (IL-4 and IL-10) cytokine response and IgG1 antibody response induced by asymptomatic antigen immunised group which has shown diverse specific immune response. Antigen diversity analysis was performed by co-culturing sera (10-fold dilution) obtained from mice immunised with Blastocystis sp. symptomatic and asymptomatic antigens and the respective Blastocystis sp. live cells through complement dependant cell cytotoxicity (CDC) assay. The sera (at 101 concentrations) from symptomatic and asymptomatic antigen immunised mice were able to specifically lyse the respective live cells with an average percentage of 82% and 86% respectively. There was almost 50% cross-reactivity iv observed between Blastocystis sp. ST3 isolates origin from the same group which proving high antigen diversity. However, there was only 17% cross-reactivity observed between the sera and cells of different group (symptomatic and asymptomatic isolates). Further in vitro studies were carried out to investigate the immune modulation triggered by Blastocystis sp. antigens towards antigen presenting cells (macrophages and monocytes). Blastocystis sp. induced apoptosis in macrophages as early as 6 hours of incubation while monocytes suppressed the secretions of pro-inflammatory cytokines through increased expressions of PD-1 during short- and long-term antigen-exposure resembling acute and chronic infection respectively. This observation implicates the immunosuppressive features of Blastocystis sp. which could be utilised to evade host innate defence mechanisms. Next, the effect of Blastocystis sp. antigen on T cell immune modulation (adaptive immunity) was assessed by introducing symptomatic and asymptomatic parasite antigens to the blood mononuclear cells (PBMCs) in vitro. The antigens resulted in elevated levels of T cell co-inhibitory molecules and reduced functional T cell pro?inflammatory cytokines (IL-2 and IFN?) suggesting that the parasite is able to cause T cell ï¿½exhaustionï¿½ or dysfunction by symptomatic and asymptomatic antigens at 83% and 94% respectively. This study underscores the importance of identifying the differences of immune responses and immunomodulation mechanisms induced by Blastocystis sp. ST3 symptomatic and asymptomatic isolates in a host. The study for the first time, had shed light on the distinct host immune response induced by Blastocystis sp. ST3 symptomatic and asymptomatic isolates implicating that these isolates could portrayed different immunopathogenesis in the host intestine. Keywords: Blastocystis sp., symptomatic, asymptomatic, Subtype 3, Immunopathogenesis.